2007
DOI: 10.1002/elps.200700421
|View full text |Cite
|
Sign up to set email alerts
|

NACE for the analysis of acrylamide in food

Abstract: An NACE method was developed for the quantitative determination of acrylamide in processed food. The method is premised on the modification of the aqueous acid-base character of acrylamide in an organic solution. Acrylamide, which is a polar molecule in aqueous solution, in a low-pH environment in ACN acquires a proton, and thereby migrates under its own electrophoretic mobility in CE. Thus, nonaqueous separation of acrylamide was achieved by employing 30 mmol/L HClO(4) in ACN as the running electrolyte. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The results showed that the method could be used for quantitative purposes on either food or environmental samples. A nonaqueous CE method was developed for the quantitative determination of AA in processed food like potato chips and French fries (Başkan and Erim 2007). The AA amount of these samples were found to be 2.95±0.11 mg/kg.…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…The results showed that the method could be used for quantitative purposes on either food or environmental samples. A nonaqueous CE method was developed for the quantitative determination of AA in processed food like potato chips and French fries (Başkan and Erim 2007). The AA amount of these samples were found to be 2.95±0.11 mg/kg.…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…Capillary electrophoresis (CE) has the characteristics of fast analysis speed and high separation efficiency, and requires a small amount of sample, making it an effective tool for the analysis of trace components in foods [65,66]. CE is based on different charge ratios of the target substance to achieve efficient separation.…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…However, the polar AAM does not have strong UV absorption and is electrochemically inactive, giving rise to a detection problem. Although the use of UV cell with extended optical path can improve detection sensitivity, the separation efficiency is greatly reduced [14,15]. The recent availability of economic semiconductor laser makes LIF an affordable solution for the determination of AAM, which requires very high detection sensitivity.…”
Section: Introductionmentioning
confidence: 99%